Newspapers Frame Julian Assange Differently. (January 2014) - Luther, Catherine A.; Radovic, Ivanka
This analysis of coverage of Assange in two U. S. and two French newspapers found that The New York Times was more critical of Wikileaks and more leery of Internet freedom of expression than was The Washington Post. LeMonde framed Assange as a journalist.